Analisis Pengendalian Kualitas Pada Produk Roti di PT. Bapak Bakery - Dewi, Ida Ayu Putu Pradnyani; Sedana Yoga, I. W. G.; Suryawan Wiranatha, A. A. P. A. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2023)
PT. Bapak Bakery is a food processing company, especially bread with various types of products. The types of product defects that are often encountered are inappropriate shape, inappropriate size and charred. The purposes of this study were to determine the level of defect in bread products at PT. Bapak Bakery, to know the factors that cause defective products that often occur in PT. Bapak Bakery, as well to formulate the recommendation of improvement efforts to overcome defective products that often occur in PT. Bapak Bakery. Data analysis used the six sigma method through five stages, namely define, measure, analyze, improve, and control (DMAIC) and followed by the Failure Mode and Effect Analysis (FMEA) method used in the Analyze stage. The results showed that the product sigma values ??1, 2, and 3 were at the level of 3.93, 3.86 and 3.09, these values ??had not yet reached the level of 6 sigma. Product sigma values ??1, 2, and 3 indicate the possibility of product defects of 7.852, 9.457 and 56.956 for one million opportunity. PT. Bapak Bakery needs to do quality control to achieve the target of zero defects. Factors causing product defects were human factors, method factors, raw material factors and machine factors. Suggestions for improvement that can be done are holding regular training for workers, including SOPs for making bread in each room of the production process, increasing supervision starting from the selection of raw materials, weighing materials, production processes, permanently listing measuring instruments on the production table, as well as the use of kanban cards and timers to simplify the baking process.